2007
DOI: 10.1152/advan.00010.2007
|View full text |Cite
|
Sign up to set email alerts
|

Does gender influence learning style preferences of first-year medical students?

Abstract: Students have specific learning style preferences, and these preferences may be different between male and female students. Understanding a student's learning style preference is an important consideration when designing classroom instruction. Therefore, we administered the visual, auditory, reading/writing, kinesthetic (VARK) learning preferences questionnaire to our first-year medical students; 38.8% (97 of 250 students) of the students returned the completed questionnaire. Both male (56.1%) and female (56.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
118
8
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(152 citation statements)
references
References 25 publications
20
118
8
4
Order By: Relevance
“…However, studies looking at gender preference for modes of learning in higher education have shown that there does not appear to be a difference. While females have been shown to prefer a broader range of stimuli than males, both genders appreciate variety in their educational experience (Shaw & Marlow, 1999;Slater, Lujan, & DiCarlo, 2007). Importantly, this subjective measurement of perceived effectiveness was supported by the performance of females in this study, with females showing an almost 3.5% greater mean course grade than males.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, studies looking at gender preference for modes of learning in higher education have shown that there does not appear to be a difference. While females have been shown to prefer a broader range of stimuli than males, both genders appreciate variety in their educational experience (Shaw & Marlow, 1999;Slater, Lujan, & DiCarlo, 2007). Importantly, this subjective measurement of perceived effectiveness was supported by the performance of females in this study, with females showing an almost 3.5% greater mean course grade than males.…”
Section: Discussionsupporting
confidence: 63%
“…Understanding how different genders respond to such a group-based learning activity could not only aid teachers in determining what strategies could prove useful for their class makeup given variable class composition, but also help educators better understand potential differences between gender for learning preference in higher education. While it has been suggested that females may respond more positively to group work than males due to their socially collaborative nature (Daniels, Creese, Hey, Leonard, & Smith, 2001), studies on pedagogy preference in higher education between genders have so far shown little difference (Shaw & Marlow, 1999;Slater, Lujan, & DiCarlo, 2007). Additionally, GPA is an important variable to include when assessing learning strategies not only to account for drastic changes in performance but to also control for trends that may in fact be quite apart from gender.…”
mentioning
confidence: 99%
“…Gender was reported to influence "student learning style" in addition to various factors including age, culture, academic achievement, and others [18]. However, data from first year medical students in Detroit showed that the numbers and types of modality combinations in the VARK questionnaire were not significantly different between genders [3]. Similarly, an study with first year medical students in Turkey found no differences across male and female students according to VARK questionnaire [15].…”
Section: Discussionmentioning
confidence: 99%
“…Hilliard and Tallett [2] defined learning style as "a predisposition on the part of some students to adopt a particular learning strategy regardless of the specific demands of the learning task". According to Slater et al [3] medical students "encounter a distinctive challenge in the rigor of their required coursework and the increased volume that constitutes the program of study". The Grasha Reichmann Student Learning Styles Scale (GR-SLSS) is considered one of the few instruments designed specifically to be used with senior high school and university students.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively homogenous population which was surveyed in this study may have tended to have less variety in these factors [19].…”
Section: Limitationmentioning
confidence: 93%